(412) Selected Bibliography on Methods Planning مختارات من المراجع حول طرق التخطيط - Hosny, A. (معهد التخطيط القومى, 2024)
This selected bibliography presents a specialized collection of literature and studies related to methods of economic and development planning. Prepared by the Institute of National Planning in 1964, the work was designed to provide researchers and specialists with a comprehensive academic reference concerning planning theories and practices. The bibliography covers major dimensions of planning thought and reflects the evolution of planning methodologies during the mid-twentieth century. The first group of references focuses on planning experiences in the Soviet Union as a model of a centrally directed economy. The cited studies examine planning organization during different developmental stages, basic principles of industrial planning, methods of industrial production planning, national balances, labor planning, and approaches for improving living standards. In addition, these references address monetary control mechanisms, accounting systems, and their relationship with economic decision-making processes. Another section addresses alternative planning techniques and theoretical approaches. These studies discuss economic programming models, forecasting methods, planning strategies, and the relationship between centralized and decentralized systems. Furthermore, they examine the conditions necessary for achieving economic efficiency under various planning structures. Contributions from leading scholars such as Tinbergen, Frisch, and Bettleheim are included to illustrate theoretical frameworks and analytical tools applied in planning research. The bibliography also includes applied studies concerning planning in the United Arab Republic (U.A.R.), emphasizing economic and social development planning, long-term development strategies, manpower planning, public budgeting, and the application of input-output models in developing economies. Attention is also given to the implementation and monitoring of five-year development plans. The significance of this bibliography lies in its integration of theoretical and practical perspectives on planning. It provides a systematic academic foundation for understanding the historical development of planning concepts and methodologies and serves as an important reference for researchers, economists, and policy makers interested in economic development and planning studies.